Modeling Land Use Change Dynamics in the Buffer Zone of Bukit Rimbang Bukit Baling Wildlife Reserve: A Business-as-Usual Simulation-Based Approach - Suandy, Indra; Harahap, Syaiful Ramadhan (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
The buffer zone of the Bukit Rimbang Bukit Baling Wildlife Reserve (BRBB WR) has been experiencing rapid land use changes due to demographic and economic pressures. This study simulated land-use change dynamics using a business-as-usual (BAU) approach to understand land transformation patterns in the absence of policy interventions. A dynamic system modeling approach was employed, with key variables including population growth, expansion of residential areas, and the extension of agriculture and plantations. The analyzed data comprised spatial land cover data from 2008 and 2019 as well as demographic data from 2019 to 2023. The simulation results indicate that without intervention, primary forests and shrublands covering approximately 1.59% and 0.62% of the study area, respectively, in 2019 will disappear before 2028. Meanwhile, secondary forests and bare lands, which occupy 18.65% and 3.83% of the area, respectively, are projected to continue declining until 2035. Conversely, plantations, agricultural land, and settlements have expanded significantly, exacerbating pressure on the ecosystem. Model validation using the Mean Absolute Error (MAE) yielded a value of 0.48%, demonstrating high accuracy in predicting land-use changes. These findings emphasize the urgent need for conservation-based policies to curb deforestation and land conversion, while promoting more sustainable resource management to maintain the ecological and socioeconomic balance in the BRBB WR buffer zone.